The Effect of Islamic Financial Literacy, Return Perception, and Risk Perception on Investment Decisions in Sharia Stocks with Experienced Regret as a Moderation Variable (Case Study on the Indonesian Muslim Merchants Association) - Husein, Muhamad (Economics & Islamic Finance Journal (ECIF), 2025)
This study aims to identify the influence of Islamic financial literacy, return perception, and risk perception on investment decisions by involving experienced regret as a moderating variable. This research is a quantitative research whose data source comes from questionnaires distributed to 100 ISMI members. The data were analyzed using partial least square technique with the help of SMARTPLS 3 software. The results showed that Islamic financial literacy, return perception, and risk perception have a positive and significant effect on investment decisions. In addition, there is a moderating role of experienced regret in strengthening the influence of Islamic financial literacy, return perception, and risk perception on investment decisions.